Addition to the flora of National Nature Park “Desniansko- Starogutsky” (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
The list of vascular plants of the National Nature Park "Desniansko-Starogutsky" was complemented. During the field researches 46 new species are educed. Five new species are educed on results of herbarium collections’ treatment. 3 spe cies are redefined, in particular it was corrected Carex buxbaumii on Carex hartmanii (a list had Carex hartmanii already). 6 new species are also mentioned in literature. Thus, the list of flora of vascular plants of National Nature Park "Desniansko-Starogutsky" is filled up on 57 species and 18 genera, and now it counts 853 species and 419 genera. Most new species present natural biotopes: meadows (10 species), forests (12) a water-bog (9). Mostly there are cultural (12), ruderal (11) and segetal (3) species. Among new species there are the rare plants listed in the Red Data Book of Ukraine: Aldrovanda vesiculosa, Utricularia minor and Epipactis palustris.
Keywords: Polissia, flora, Desniansko-Starogutskiy, protected area, addition to the flora.